Evaluation of Public Health Veterinary Services’ Availability for Rabies in Namibia (2010-2020) - Efraim LN; Sheehama J; Haufiku D (Disease and Health: Research Developments Vol. 8, 2025)
Background: Rabies is a neglected zoonotic viral disease that occurs worldwide except in Antarctica. It spreads to humans through the saliva of infected animals. The virus is usually transmitted through bite, which is the common cause of rabies worldwide. Rabies is endemic throughout the world and they mostly affect poor and vulnerable populations who live in remote areas. Death is rarely reported and human vaccines and immunoglobulins exist for rabies, however, they are not accessible to needy people. About 60,000 people die per year mostly in Africa. Domestic animals especially dogs are responsible for the transmission of the virus through bites, scratches or saliva. Clinical symptoms may include unexplained tingling, fever, headache, and confusion. As the virus spreads to the central nervous system fatal inflammation of the spinal cord and brain develops. Aim: The aim of the study is to review the availability of Public Health Veterinary Services for Rabies prevention in Namibia. Methods: A scoping review was conducted, and data were collected from five databases namely PubMed Central, Biomedical Central, HINARI, Google Scholar and EBS Cohost. The articles published between 2010 and 2020 were only included, and a total of ten articles met the study’s objectives. Results: The studies conducted revealed that more effort was put into delivering vaccines to the communities, and the educational campaigns were done accordingly. Although educational programs were provided and other public health services it was discovered that 74% of dog owners expressed their knowledge and 24% had never heard about rabies and had never taken their dogs for vaccine. Most of the public health services are available, especially the vaccine and campaign, people are ignorant and fewer of them do not understand. Conclusion: Vaccine is the most effective way of eliminating rabies. Educational programs and campaigns are mostly done when they start doing outreach points for vaccines. Countries like Ghana indicated that health promotion and campaigns were the main targets in the years 2015-2017 in order to fight against the rabies virus. Local vaccination campaigns should make an effort to eliminate the spread of rabies between dogs and humans, dog to dog. Awareness campaigns and educational programs should focus more on providing the right and updated information in order to reduce the spread of rabies in humans and dogs. In view of the Public Health importance of rabies, the government, NGOs and community people need to put more effort into the prevention and controlling rabies by making sure dogs are vaccinated against rabies, and dog owners are given all the information on rabies so that they can help meet the government halfway on fighting rabies.